Entre jurisdição e expectativas : uma reflexão sobre as expectativas em torno da atuação do juíz no processo penal - Castro, Matheus Borges e (2023)
The present research aims to analyze how the loads of expectations condition and influence the performance of the judge in the scope of the criminal procedure, with a view to the impartiality that is required of him, especially when considering the challenges that are so characteristic of the Brazilian criminal procedure while founded in an authoritarian field. In this sense, it is developed from three chapters which, respectively, deal with: 1) the accusatory criminal procedural system thought from the Brazilian context, the necessary constitutional reading for the criminal procedure, the great relevance of the function and place of the judge in criminal procedure, as well as the influences arising from this current authoritarian tradition; 2) the frame of expectations surrounding the performance of the criminal judge, how expectations influence and condition the judge to correspond and meet such expectations that are projected, having chosen three orders of expectations to dialogue with, namely, social expectations, legal/normative expectations and probatory expectations, a dialogue that underlies and directs the elementary issue of judicial impartiality; 3) the tensioning of these expectations from the need to ensure and preserve the impartiality of the judge in criminal procedure, understanding impartiality as the supreme principle of criminal procedure and as an indispensable legal category, in addition to the respective challenges and its (in)effectiveness in the Brazilian context, promoting a reflection based on the emblematic example of the former judge and former Minister Sérgio Moro, who in this proposed dialogue and the respective theoretical framework developed reveal the impracticability of judicial impartiality in the context of the Brazilian criminal procedure due to the lack of conditions of possibilities for this, from the cultural to the structural perspective, which implies the urgent need for a global reform of the Code of Criminal Procedure concomitant with the embarrassment and overcoming of the authoritarian-inquisitorial culture for the accusatory-democratic vigor that is aimed.